'The Germans are back': Euroscepticism and anti-Germanism in crisis-stricken Greece†. Issue 1 (2nd January 2017) - Michailidou, Asimina
ABSTRACT: The Eurocrisis has generated a deep and ongoing politicization of the EU within and across national public spheres, fuelling age-old and new political and social conflicts, which in turn shape public perceptions of crisis and the legitimacy of 'crisis government'. Focusing on Greece, an EU member state at the epicentre of the crisis, this paper examines how the European polity was contested in the first five years (2009–2013) of the 'Eurocrisis'. During this period, anti-German stereotypes resurfaced in the Greek public sphere in parallel with increasingly mainstream Euroscepticism. Nevertheless, analysis of news and social media content from this period shows that beneath this new-found scepticism towards the EU and Germany's role in it lie two much broader narratives: that of the power struggle between the people and the political elites; and that of an epic clash between diametrically different political ideologies.